2019
DOI: 10.1186/s13063-019-3760-2
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement desensitization and reprocessing (EMDR) therapy for posttraumatic stress disorder in adults with serious mental illness within forensic and rehabilitation services: a study protocol for a randomized controlled trial

Abstract: BackgroundEye movement desensitization and reprocessing (EMDR) is an evidenced-based treatment for posttraumatic stress disorder (PTSD). Forensic mental health services provide assessment and treatment of people with mental illness and a history of criminal offending, or those who are at risk of offending. Forensic mental health services include high, medium, and low-security inpatient settings as well as prison in-reach and community outpatient services. There is a high prevalence of PTSD in forensic settings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…EMDR therapy has been used in different populations for the treatment of posttraumatic stress disorder (26)(27)(28), showing benefits in improving sleep quality and quality of life and decreasing symptoms associated with comorbid PTSD (29)(30)(31). Similarly, EMDR therapy has been applied in people with serious mental illnesses, such as psychosis (32), and in forensic and rehabilitation services (33,34).…”
Section: Introductionmentioning
confidence: 99%
“…EMDR therapy has been used in different populations for the treatment of posttraumatic stress disorder (26)(27)(28), showing benefits in improving sleep quality and quality of life and decreasing symptoms associated with comorbid PTSD (29)(30)(31). Similarly, EMDR therapy has been applied in people with serious mental illnesses, such as psychosis (32), and in forensic and rehabilitation services (33,34).…”
Section: Introductionmentioning
confidence: 99%
“…Much research has been carried out to evaluate the effectiveness of EMDR on a wide range of mental health difficulties across different groups and settings. Several studies found EMDR to be effective in reducing PTSD, depression and anxiety and increasing quality of life across a wide range of age groups and populations including clinical and nonclinical groups (Acarturk et al, 2016; Ahmad, Larsson, & Sundelin‐Wahlsten, 2007; de Roos et al, 2011, 2017; Every‐Palmer et al, 2019; Horst et al, 2017; Karatzias et al, 2019; Ostacoli et al, 2018; Ter Heide, Mooren, Van De Schoot, De Jongh, & Kleber, 2016; Van Den Berg et al, 2018). Several systematic reviews and meta‐analyses have attested its efficacy across a broad range of difficulties, including PTSD (Bisson et al, 2007; Chen, Zhang, Hu, & Liang, 2015; Ehring et al, 2014; Khan et al, 2018; Korn, 2009), medically unexplained symptoms (van Rood & de Roos, 2009), depression (Wood & Ricketts, 2013), anxiety (Yunitri et al, 2020), distress due to natural disasters (Natha & Daiches, 2014) and chronic pain (Tesarz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Given the high risk for the development of post-traumatic symptoms during the pandemic (Huang et al 2020), trauma-informed care approaches should be added to the interventions routinely delivered in Italian forensic psychiatry settings (Lewis and Ireland, 2019). A number of empirically validated psychotherapeutic approaches have been developed to reduce traumarelated symptoms such as Eyes Movement Desensitization Reprocessing (EMDR), or to prevent them such as mindfulness-based protocols, both for the offenders and the psychiatric staff (Every-Palmer et al 2019;Howell et al 2010).…”
Section: The Impact Of the Covid-19 Pandemic In Italymentioning
confidence: 99%